To solve the system of equations using the substitution method, we have the equations:
- \( x = y - 4 \)
- \( x + 8y = 2 \)
We'll first substitute the expression for \( x \) from the first equation into the second equation.
Substituting \( x = y - 4 \) into the second equation:
\[ (y - 4) + 8y = 2 \]
Now, simplify the equation:
\[ y - 4 + 8y = 2 \] \[ 9y - 4 = 2 \]
Next, add 4 to both sides:
\[ 9y = 6 \]
Now divide by 9:
\[ y = \frac{6}{9} = \frac{2}{3} \]
Now that we have \( y \), we can find \( x \) using \( x = y - 4 \):
\[ x = \frac{2}{3} - 4 \] \[ x = \frac{2}{3} - \frac{12}{3} = \frac{2 - 12}{3} = \frac{-10}{3} \]
So, the solution for the system is:
\[ \left( -\frac{10}{3}, \frac{2}{3} \right) \]
Therefore, the response \( (−\frac{10}{3}, \frac{2}{3}) \) is not one of the options presented. The correct substitution yields the coordinates \( \left( -\frac{10}{3}, \frac{2}{3} \right) \).
Please verify the option formats or check if there was an error. The answer might not match the provided options directly.